3D game development cube-It : back end web app development - Hshieh, Yeu Yann (2016)
Cube-It is a new state-of-the-art joining device and system created and designed by PABensen Pte. Ltd., a design company engaged in developing thought provoking artistic objects and innovation functional products that bridge the fields of art, science and technology. This Final Year Project is an industrial collaboration project with PABensen Pte. Ltd.